Depletion controlled surface deposition of uncharged colloidal spheres from stable bulk dispersions. Issue 17 (30th March 2016) - Ouhajji, Samia; Nylander, Tommy; Piculell, Lennart; Tuinier, Remco; Linse, Per; Philipse, Albert P.
Abstract : A window of interaction strength exists at which surface adsorption is significant while bulk aggregation is negligible. Abstract : The competition between surface adsorption and bulk aggregation was investigated for silica colloids dispersed in cyclohexane in contact with hydrophobized silica substrates. Central to this study is that the colloids and surfaces have the same material and surface properties. Colloid–colloid and colloid–surface interactions were controlled by addition of polymers providing depletion interaction. Bulk instability was determined by turbidity and viscosity measurements and surface adsorption by ellipsometry measurements. At increasing polymer concentration, strong surface adsorption occurred at polymer concentrations below that required for bulk phase separation. Complementary Monte Carlo simulations with the use of a new weak depletion theory support quantitatively the experimental observation of the existence of an interval of interaction strength at which aggregation in bulk is negligible while surface adsorption is substantial.